Habitat characteristics and biodiversity of nekton in the Alas-Singkil River Basin, Northern Sumatra, Indonesia - AHMAD MUHTADI; RUSDI LEIDONALD; ASTRID DEWINTA FAUZIA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Muhtadi A, Leidonald R, Fauzia AD. 2023. Habitat characteristics and biodiversity of nekton in the Alas-Singkil River Basin, Northern Sumatra, Indonesia. Biodiversitas 24: 3673-3689. The Alas-Singkil watershed ecosystem is an essential habitat for the diversity of flora and fauna in the North Sumatra region. This study aims to describe the habitat characteristics and distribution of ichthyofauna in the Alas-Singkil watershed. Observations and data collection were carried out in 2021-2022 in all river segments in the Alas-Singkil watershed, including the downstream, swamp, oxbow lake, middle, upstream, and tributaries. Habitat characteristics in the Alas-Singkil watershed are very diverse. Some swamps in the main river's lower to middle reaches allow the ichthyofauna to migrate laterally. In the middle of the main tributaries (sub-watersheds) to the upstream (most) have habitat characteristics dominated by sedimentary rock substrates with relatively moderate-strong currents. The upper reaches of the main river are dominated by rocky substrates with clear, low-medium flowing waters. During observations in the Alas-Singkil watershed, 99 species of fish from 39 families, 9 species of shrimp, 1 species of freshwater crab, 1 species of freshwater turtle, and 1 species of crocodile were collected. Spotted barb (Barbodes binotatus), Blue panchax (Aplocheilus panchax), and Mahseer fish are fishes often found and widely distributed in the Alas-Singkil watershed. The nekton found in the Alas-Singkil watershed is included in the Least Concern (LC) category at 71% and Data Deficient (DD) at 14%. However, there are 2 species (2%) in the Endangered (EN) category and 6 species (5%) in the Vulnerable (VU) category; Ompok brevirictus and Clarias microspilus are species categorized as Endangered Species.